Effects of polishing systems on the surface roughness of tooth-colored materials - Ugur Erdemir; Esra Yildiz; Meltem Mert Eren; Alev Ozsoy; Fulya Toksoy Topcu (Elsevier, 2013)
Background/purpose: Polishing systems may affect the surface characteristics of the tooth-colored restorative materials. In this in vitro study, we evaluated the surface roughness of various tooth-colored restorative materials after polishing them with three different polishing systems. Materials and methods: The tooth-colored restorative materials evaluated were conventional glass-ionomer cement, compomer, microhybrid, and nanofil composite. In total, 112 specimens (10 mm in diameter and 2 mm thick) were prepared in a metal mold using four different tooth-colored restorative materials. After the light curing and setting cycle, seven specimens from each group which received no polishing treatment were used as controls. Specimens were randomly polished with Sof-Lex disks, Poli-pro disks, and the HilusterPlus systems for 30 seconds. The mean surface roughness of each polished specimen was determined with a profilometer and examined using scanning electron microscopy. Data were analyzed using a two-way analysis of variance and Bonferroni's post-hoc multiple-comparison test, with a probability level of 0.05. Results: According to the two-way analysis of variance, the type of tooth-colored materials, polishing technique, and their interactions were statistically significant (P < 0.001). The smoothest surfaces of all materials were obtained with the Mylar strip. Glass-ionomer cement demonstrated statistically significantly higher Ra values (1.36 ± 0.77) than the other restorative materials tested (P < 0.05). Compomer (0.65 ± 0.28) produced the smoothest surface and did not significantly differ from the microhybrid composite (0.78 ± 0.39; P > 0.05). No significant difference was observed between the microhybrid and nanofil composites (1.08 ± 0.83; P > 0.05). According to the scanning electron microscopy observations, the surface irregularities of the materials were consistent with the surface roughness profilometric findings. Conclusion: The effectiveness of a polishing system on the surface roughness depends on both the polishing system and restorative material.